MEANS AND METHODS OF FORMING INTERTEXTUALITY - Do‘smuradova , Yulduz To‘ychi qizi (Educational Research in Universal Sciences, 2023)
This article discusses the means and methods of forming intertextuality. Quote, allusions are said to be part of intertextuality definitions and classifications are explained by examples taken from the works of foreign writers. Focuses on interpreting what many scholars have said about intertextuality. Intertextuality is a very broad concept, which has been studied not only in literature, but also in linguistics and is still being researched. Through this article, we tried to express our thoughts.